Antiviral activity of chrysin against influenza virus replication via inhibition of autophagy - Kim, Seong Ryeol; Jeong, Myeong Seon; Mun, Seo Hyeon; Cho, Jaewon; Seo, Min Duk; Kim, Hyoungsu; Lee, Jooeun; Song, Jae Hyoung; Ko, Hyun Jeong (Viruses, 2021)
Influenza viruses cause respiratory infections in humans and animals, which have high morbidity and mortality rates. Although several drugs that inhibit viral neuraminidase are used to treat influenza infections, the emergence of resistant viruses necessitates the urgent development of new antiviral drugs. Chrysin (5,7-dihydroxyflavone) is a natural flavonoid that exhibits antiviral activity against enterovirus 71 (EV71) by inhibiting viral 3C protease activity. In this study, we evaluated the antiviral activity of chrysin against influenza A/Puerto Rico/8/34 (A/PR/8). Chrysin significantly inhibited A/PR/8-mediated cell death and the replication of A/PR/8 at concentrations up to 2 µM. Viral hemagglutinin expression was also markedly decreased by the chrysin treatment in A/PR/8-infected cells. Through the time course experiment and time-of-addition assay, we found that chrysin inhibited viral infection at the early stages of the replication cycle. Additionally, the nucleoprotein expression of A/PR/8 in A549 cells was reduced upon treatment with chrysin. Regarding the mechanism of action, we found that chrysin inhibited autophagy activation by increasing the phosphorylation of mammalian target of rapamycin (mTOR). We also confirmed a decrease in LC3B expression and LC3-positive puncta levels in A/PR/8-infected cells. These results suggest that chrysin exhibits antiviral activity by activating mTOR and inhibiting autophagy to inhibit the replication of A/PR/8 in the early stages of infection.
Keywords: A549 Cells; Animals; Antiviral Agents; Autophagy; Dogs; Flavonoids; Humans; Influenza A virus; Influenza, Human; Madin Darby Canine Kidney Cells; Neuraminidase; Viral Proteins; Virus Replication; Antiviral activity; Autophagy; Chrysin; Influenza A/Puerto Rico/8/34; MTOR